Investigating adsorptive deep desulfurization of fuels using metal-modified adsorbents and process intensification by acoustic cavitation - Suryawanshi, N.B.; Bhandari, V.M.; Sorokhaibam, L.G.; Ranade, V.V. (Industrial and Engineering Chemistry Research, 2018)
The harmful impact on the environment due to SOx emissions from fuels and increasingly strict norms over the years have amplified deep-desulfurization challenges, consequently enhancing attractiveness of adsorptive separations. The present work focuses on investigating metal modifications and process intensification using acoustic cavitation for improving sulfur removal behavior and selectivity. The proof of concept was elucidated using two model adsorbents: one commercial Shirasagi TAC adsorbent and another newer adsorbent derived from Cassia fistula biomass. Single- and double-metal modifications were studied using zinc, cobalt, nickel, and copper. An attempt was made to further improve the sulfur removal using process intensification using acoustic cavitation coupled with adsorption. The removal of three refractory sulfur compounds (viz. thiophene, benzothiophene, and dibenzothiophene) was studied, and the performance was compared for both single- and double-metal modifications apart from process intensification. In the case of TAC, a high capacity for sulfur removal, up to 23 mg S/g, was obtained, especially for dibenzothiophene. Process intensification using cavitation coupled with adsorption further improved sulfur removal to the extent of 100%, and for metal-modified TAC, a capacity increase up to 38 mg S/g for dibenzothiophene was obtained. The results indicate that the combined effect of metal modification and process intensification can substantially improve the sulfur-removal efficiency of carbon adsorbents.